1985
DOI: 10.1093/ije/14.3.378
|View full text |Cite
|
Sign up to set email alerts
|

Type of Occupation and Near-Future Hospitalization for Myocardial Infarction and Some Other Diagnoses

Abstract: Using three different registers a cohort study was undertaken to describe the relationship between type of occupation and hospitalization. A total of 958 096 subjects aged 20-64 years were followed-up for one year regarding inpatient care. Several significant associations between type of occupation and incidence of hospitalization for different diagnoses were observed. Male subjects employed in occupations where a high proportion reported a combination of hectic work and few possibilities to learn new things w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
88
1
5

Year Published

1990
1990
2009
2009

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 227 publications
(98 citation statements)
references
References 0 publications
4
88
1
5
Order By: Relevance
“…Stress within working life has been implicated as a casual factor of ill health, particularly in relation to metabolic and cardiovascular disease (Alfredsson et al, 1985;Hammar et al, 1994;Siegrist, 1996;Theorell et al, 1998). Recent data from a Japanese prospective study estimates the risk for a cardiovascular event to be 2.89 in groups with high job strain (Uchiyama et al, 2005) Results from a study by Amelsvoort et al (2000) indicated that one of the mechanisms behind the increased risk of myocardial infarction might be a shift in the cardiac balance; subjects with higher job strain had a shift towards sympathetic dominance.…”
Section: Work Related Stress and Stress Related Diseasesmentioning
confidence: 99%
“…Stress within working life has been implicated as a casual factor of ill health, particularly in relation to metabolic and cardiovascular disease (Alfredsson et al, 1985;Hammar et al, 1994;Siegrist, 1996;Theorell et al, 1998). Recent data from a Japanese prospective study estimates the risk for a cardiovascular event to be 2.89 in groups with high job strain (Uchiyama et al, 2005) Results from a study by Amelsvoort et al (2000) indicated that one of the mechanisms behind the increased risk of myocardial infarction might be a shift in the cardiac balance; subjects with higher job strain had a shift towards sympathetic dominance.…”
Section: Work Related Stress and Stress Related Diseasesmentioning
confidence: 99%
“…This work was presented at the 116th Annual Meeting of the American Public Health Association, in Boston, Massachusetts, November [13][14][15][16][17] 1988.…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…Tests of these models have been carried out more often in studies of men than in studies of women, and therefore some authors question their applicability to women (8). The few prospective studies of working women found that high strain at work increased the risk of cardiovascular disease in the United States (9) and Sweden (10) and increased the risk of stroke (lo), problem drinking (lo), and elevated blood pressure (1 1,12). Less is known about the impact of iso-strain on women's health because prospective evidence is only available for men (4).…”
mentioning
confidence: 99%